A new source of the midlatitude ionospheric peak density structure revealed by a new Ionosphere‐Plasmasphere model - Maruyama, Naomi (2016)
The newly developed Ionosphere‐Plasmasphere (IP) model has revealed neutral winds as a primary source of the “third‐peak” density structure in the daytime global ionosphere that has been observed by the low‐latitude ionospheric sensor network GPS total electron content measurements over South America. This third peak is located near −30° magnetic latitude and is clearly separate from the conventional twin equatorial ionization anomaly peaks. The IP model reproduces the global electron density structure as observed by the FORMOSAT‐3/COSMIC mission. The model reveals that the third peak is mainly created by the prevailing neutral meridional wind, which flows from the summer hemisphere to the winter hemisphere lifting the plasma along magnetic field lines to higher altitudes where recombination is slower. The same prevailing wind that increases the midlatitude density decreases the low‐latitude density in the summer hemisphere by counteracting the equatorial fountain flow. The longitudinal variation of the three‐peak structure is explained by the displacement between the geographic and geomagnetic equators.